The influence of combined abdominal and thoracic trauma on the bile excretory function of the liver in the period of early manifestations of traumatic disease and their correction with thiotriazoline - O. A. Zachepa; A. A. Hudyma; Y. I. Sushko (Kazimierz Wielki University, 2019)
Introduction. Traumatism is one of the challenging issues of today's urban society. Multiple and combined lesions, which are characterized by significant severity and high mortality and lead to multiorgan dysfunction and insufficiency, dominate the structure of traumas. In recent years studies of the functional state of the liver have been widely used as a model for development of multiorgan dysfunction in conditions of severe experimental trauma. Objective of the research: to find out the character of disorders of bile excretory function of the liver in conditions of the combined abdominal and thoracic trauma of rats in the early period of a traumatic disease, and to evaluate the effectiveness of their correction with thiotriazoline. Materials of the research and their discussion. The experiments were conducted on 86 non-linear white male rats weighing 200-220 g. All animals were divided into five groups: a control and four experimental ones. Injuries were inflicted under thiopental sodium anesthesia. The control group included intact animals, which were only injected into anesthesia. Animals with simulated thorax trauma were in the first experimental group. In the second experimental group a blunt abdominal trauma was simulated. In the third experimental group, these traumas were combined. In the fourth experimental group of animals with a combined trauma, thiotriazoline was administered intraperitoneally at a dose of 9.1 mg per kg-1. In 1, 3, and 7 days after injuries were caused under conditions of thiopental sodium anesthesia, the common bile duct was catheterized in animals and bile was taken for 60 minutes. The rate of bile excretion was set. The concentration of total bile acids and conjugated bilirubin was determined in bile, and their excretion rate was calculated. Results of the research and their discussion. In conditions of causing isolated thoracic trauma, abdominal trauma and their combination, a significant disorder of the bile-excreting function of the liver emerges, that is, first of all, manifested by a decrease in the speed of bile excretion and excretion of its main components - cholates and conjugated bilirubin. The severity of liver dysfunction can be divided as follows: isolated thoracic trauma ← isolated abdominal trauma ← combined trauma. In conditions of isolated thoracic trauma, the investigated parameters in comparison with the control reach a minimum level up to the 3d day and normalize to the 7th day. After causing an isolated abdominal trauma the rate of bile excretion and the rate of excretion of total bile acids decrease after a day. However, all investigated parameters reach a minimum value after 3 days and remain at the same level up to the 7 day. After a combined trauma, the indicators gradually decrease to the 7th day and in each subsequent period become significantly smaller than in the previous one. The use of thiotriazoline for the correction of the detected disorders in the group of animals with combined trauma compared with animals without correction contributed to a significant increase in the rate of bile excretion, excretion of total bile acids and conjugated bilirubin. Although, by the 7th day the indicators did not reach the level of the control group, it can be stated that thiotriazoline exerts a positive effect on the biliary function of the liver. Conclusions. Combined abdominal and thoracic trauma contributes to a greater reduction in liver functional capacity compared with isolated lesions. They are based on the suppression of the rate of bile excretion and excretion of total bile acids and conjugated bilirubin. The use of thiotriazoline at a dose of 9.1 mg / kg-1 for animals with combined abdominal trauma is accompanied by a significant reduction in biliary function of the liver.